Cyathodium denticulatum Udar et Srivastava: A rare liverwort new to Chhattisgarh, Central India - Dixit, Ashwini Kumar; Kerketta, Mery Aradhna (Current Botany, 2020)
This article reports the occurrence of the thalloid liverwort Cyathodium denticulatum Udar et Srivastava was collected first time from the Achanakmar – Amarkantak Biosphere Reserve (AABR) Bilaspur, Chhattisgarh. It is shown that Cyathodium denticulatum a narrow Himalayan endemic has been reported earlier from Darjeeling, India. There is no record of its occurrence from central India. Cyathodium denticulatum is a rare species known only from eastern Himalayan region. A key to related Indian taxa and taxonomic description is provided.